Dimensions of accessibility benefits - Andrés Monzón de Cáceres; Elena López (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper addresses the problem of involuntary social exclusion resulting from mobility constraints by proposing a conceptual model for the interaction between transport and wellbeing. Providing accessibility for all yields widely shared benefits that are largely overlooked by traditional appraisal methods. While some see the ultimate aim of transport policy as increasing wellbeing, an agreed model of how these two interact does not currently exist.
Keywords: 330